(untitled) (KULT_online, 2021)
This review analyzes the book by Corinne Geering Building a Common Past: World Heritage in Russia under Transformation, 1965–2000. Based on a multi-layer approach, the author presents a comprehensive history of the late Soviet and early Russian state practices of heritage preservation from an international perspective. The monograph constitutes a valuable contribution to the historiographies of many historical fields, reconsidering the boundaries of a national framework and the Cold War narratives.